Family participation in pregnancy: integrative review - Laís Antunes Wilhelm; Luiza Cremonese; Críslen Malavolta Castiglioni; Martha Helena Teixeira de Souza; Maria Denise Schimith; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2017)
Aim: To identify family participation in pregnancy, in scientific production. Method: integrative literature review, in which a search, in April 2017, with the descriptors family relations and pregnancy was performed, in the databases Literature Latin American and the Caribbean in health sciences, and Nursing database U.S. National Library of Medicine. Twelve articles published from 2004 to 2016, about family relationships and pregnancy, were selected from full texts in original research and available online free of charge. Results: the family takes part in the pregnancy as: protecting and supporting, encouraging pregnant women to perform self-care by means of information and guidance, emotional and psychological support, and with financial aid. Conclusion: pregnancy is a family event and an understanding about the participation of the family in the gestational process can contribute to quality assistance.